A Super Specialty Hospital: What Went Wrong? - Costa, Juao C. (Prabandhan: Indian Journal of Management, 2015)
The culture of philanthropy is as old as India itself, which has a history spanning thousands of years. One who enjoys abundance without sharing it with others is indeed a thief, says the Bhagavad Gita. According to the New Companies Act, 2013, corporations need to spend 2% of their last 3 years’ average profits on CSR activities starting the current fiscal year. The case study is about a project started by a wealthy family of Kolkata to provide medical facilities to middle-class people. From a modest beginning of a polyclinic to a mega super specialty hospital and the closure of the same within a month is the gist of the case. The case highlighted the unethical and unprofessional attitude of employees, especially the doctors who were supposed to be highly qualified in the field of social work. The case study revealed why being hands-on at a job and technical expertise are a must for the success of any project. A project- social or otherwise - needs people who are sincere and hard working. The doctors and the staff appointed by the management lacked the above qualities. The doctors as well as other employees misused the infrastructure of the hospital for their personal gains, which was disapproved by the management. This led to the closure of the hospital and thus put the middle class needy people in inconvenience.